Self management as the key to the success of a modern health manager - Yunger, Vitaly; Hbur, Zoryana; Krylova, Iryna (ScienceRise: Medical Science, 2022)
Highlights the essence of the concept of “self-management” and provides its author’s interpretation. The goals and objectives of self-management in general and separately in the field of health care are considered. It was found that in order to effectively manage the staff of a health care institution, the manager, first of all, needs to know the science and art of self-management. General and local principles of science and practice of self-management are indicated. The aim of the article is to develop and analyze the main features of self-management as the basis of success of a modern health care manager. Materials and research methods are general scientific research methods such as systems analysis, comparison, generalization, swat analysis, forecasting. Studying the already studied components of the selected topic, such research methods as generalization, comparison, systems analysis were used. The basis for the study were the works of domestic and foreign scientists. Results: the article establishes that self-management helps the leader: rationally organize their work and the work of their subordinates; realize professional and life goals; avoid stressful situations; increase efficiency; enjoy the work done. An analysis of the scientific literature has led to the conclusion that strong leadership is important to ensure the success of any medical institution. A manager who pays due attention to self-development is the key to the success of a healthy atmosphere in the team. Research indicates a high level of professionalism and creativity achieved by managers only when they have a need for professional self-development, self-improvement, as well as when they show a motivational and value attitude to themselves as a subject of medical activity. Conclusions. Summarizing the above, it should be emphasized that self-management certainly affects the development of the modern manager of health care, so the following suggestions for the implementation of this method: to overcome administrative barriers to maintaining old management methods; to avoid problems caused by the inertial nature of public consciousness; reduce the level of conflict in the team; to overcome differences in professional competence; instill immunity to the fear of sanctions of the team - ridicule, overt and covert condemnation, ignorance